Efektivitas Terapi Non-Farmakologi Pada Pasien Hipertensi - Nadiya Widda Mawaddah; Damayanti, Ervina; Pardilawati, Citra Yuliyanda (CV. Jasa Sukses Abadi, 2024)
Hypertensive disease is the leading cause of early death worldwide. Hypertension is a common chronic medical condition characterized by sustained increases in arterial pressure. The high risk of side effects in the use of antihypertensive medicine for a long period of time causes non-pharmacological therapy of hypertension to be an alternative choice. This study aims to determine the effectiveness of non-pharmacological therapy in hypertensive patients in reducing and controlling normal blood pressure. The study used a literature review method with data sources of international scientific journals and articles using the PubMed database. The information search strategy used a combination of keywords such as